1996
DOI: 10.1152/jappl.1996.81.4.1535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxic pulmonary vasoconstriction on pulmonary gas exchange

Abstract: Several reports have suggested that hypoxic pulmonary vasoconstriction (HPV) might result in deterioration of pulmonary gas exchange in severe hypoxia. We therefore investigated the effects of HPV on gas exchange in normal and diseased lungs. We incorporated a biphasic HPV stimulus-response curve observed in intact dogs (S. Brimioulle, and R. Lejeune, J.L. Vachièry, M. Delcroix, R. Hallemans, and R. Naeije, J. Appl. Physiol. 77: 476-480, 1994) into a 50-compartment lung model (J.B. West, Respir. Physiol. 7: 88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…They concluded that HPV might "increase the blood flow to better aerated lung areas, which leads to improved conditions for the utilization of alveolar air". HPV shunts blood from poorly oxygenated areas to better ventilated lung segments, thereby optimizing ventilation-perfusion matching, reducing shunt fraction and optimizing systemic O 2 delivery in conditions such as atelectasis and pneumonia (Brimioulle et al, 1996). HPV onsets within seconds of moderate hypoxia and reverses quickly on restoration of normoxic ventilation.…”
Section: Pathogenesismentioning
confidence: 99%
“…They concluded that HPV might "increase the blood flow to better aerated lung areas, which leads to improved conditions for the utilization of alveolar air". HPV shunts blood from poorly oxygenated areas to better ventilated lung segments, thereby optimizing ventilation-perfusion matching, reducing shunt fraction and optimizing systemic O 2 delivery in conditions such as atelectasis and pneumonia (Brimioulle et al, 1996). HPV onsets within seconds of moderate hypoxia and reverses quickly on restoration of normoxic ventilation.…”
Section: Pathogenesismentioning
confidence: 99%
“…HPV is considered important for local matching of blood perfusion to ventilation and improves pulmonary gas exchange efficiency (Von Euler and Liljestrand, 1946;Dawson, 1984;Brimioulle et al, 1996). The primary site of constriction is the small muscular resistance arteries (Weir and Archer, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The complex abnormalities in gas exchange that occur are multiple, but the literature remains unassertive to elucidate the underlying mechanisms (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of O 2 is jeopardized when this equilibrium is altered and this proportion is reduced (2,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation